REAKSI INVESTOR TERHADAP PUBLIKASI LAPORAN KEUANGAN DI MEDIA MASSA PADA PERUSAHAAN PUBLIK - SHANTI S (Jurnal Bisnis dan Akuntansi, 2012)
It is widely known that financial statement provide accounting information helping the investor to evaluate the company financial performance. Company value could be drawn by accounting information in the financial statement. The availability of this information can help the investor to make investment decision. To prove it, this research analyzes and tests the content of the accounting information in financial statement that published in newspapers. The testing for the investment performance could be reflected by the trading volume and the stock price of the companies that listing in BEJ, with total samples 51 companies from 2005 till 2007. First research has objective to analyze the influence of the financial statement published to the trading volume activity. This analysis is for all the samples and clustered by industry. The Result of the analysis during 5 days before and 5 days after the published is only has a significant difference trading volume for basic industry. Second research has objective to analyze the influence of the financial statement published to the excess return. The result of this event window for 11 days around the published date shows that there is a significant difference for stock price for the 2 days periods before the published. The significant level is lower than 0,05, it means reject Ho. In conclusion, the published of the financial statement is significant influence the excess return.